1, 7‐Di‐tert‐butyl‐Substituted aza‐BODIPYs by Low‐Barrier Rotation to Enhance a Photothermal‐Photodynamic Effect. Issue 2 (10th November 2021) - Su, Yajun; Hu, Qiao; Zhang, Dongxiang; Shen, Yue; Li, Sicheng; Li, Ran; Jiang, Xin‐Dong; Du, Jianjun
Abstract: 1, 7‐Di‐ tert ‐butyl‐substituted aza‐BODIPYs (tBu‐azaBDP ) were successfully obtained for the first time. The structures of tBu‐azaBDP and Ph‐azaBDP were confirmed by X‐ray crystal analysis, and tBu‐azaBDP 2 is more twisted than Ph‐azaBDP 5. tBu‐azaBDP s have significant photo‐stability and enhanced water solubility. tBu‐azaBDP s possess excellent optical properties, such as high molar extinction coefficients, broad full width half maxima, and large Stokes shifts, which is comparable to those of the parent dye Ph‐azaBDP . Although the low‐barrier rotation of the distal ‐tBu groups in tBu‐azaBDP s results in low quantum yield, photothermal conversion efficiency and singlet oxygen generation ability of tBu‐azaBDP s are more effective than those of Ph‐azaBDP, which is highly desirable for a photothermal‐photodynamic therapy agent. Abstract : 1, 7‐Di‐ tert ‐butyl ‐substituted aza‐BODIPYs (tBu‐azaBDP s) were successfully prepared for the first time. Although the low‐barrier rotation of the distal ‐tBu groups in tBu‐azaBDP s results in low quantum yield, photothermal conversion efficiency and single oxygen generation ability of tBu‐azaBDP s are effective than those of Ph‐azaBDP, which is highly desirable for a photothermal‐photodynamic therapy agent.